Understanding variability in greenhouse gas emission estimates of smallholder dairy farms in Indonesia - Apdini, Titis; Al Zahra, Windi; Oosting, Simon J; Boer, Imke J.M. de; Vries, Marion de; Engel, Bas; Middelaar, Corina E.M. van (Springer, 2021)
Purpose Life cycle assessment studies on smallholder farms in tropical regions generally use data that is collected at one moment in time, which could hamper assessment of the exact situation. We assessed seasonal differences in greenhouse gas emissions (GHGEs) from Indonesian dairy farms by means of longitudinal observations and evaluated the implications of number of farm visits on the variance of the estimated GHGE per kg milk (GHGEI) for a single farm, and the population mean.